Simian virus 40 small tumor antigen and an amino-terminal domain of large tumor antigen share a common transforming function. - Montano, X (1990)
The 82-residue amino-terminal sequences of simian virus 40 large tumor antigen (TAg) and small tumor antigen (tAg) are identical. Genetic analysis of TAg lacking amino acids 1-82 revealed that it was transformation-defective, as revealed by the agar growth assay, except when introduced in the presence of tAg. Since the latter, alone, lacks overt transforming activity, it would appear that the function of the sequence common to TAg and tAg is necessary, but not sufficient, for TAg transforming activity and that tAg can provide that function or its equivalent in trans. Thus, tAg may, in part, be viewed as a "portable" copy of a TAg functional domain.